The Influence Of Leadership, Service Quality, Work Environment And Work Motivation On Employee Performance Pt. Sharia People's Financing Bank (Bprs) Fadhilah Bengkulu City - Yeni, Sela Rahma; Fitriano, Yun; Astuty, Kamelia (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The aim of this research is to determine the influence of leadership, service quality, work environment and work motivation on the performance of employees of PT Bank Perkreditan Rakyat Syariah (BPRS) Fadhilah, Bengkulu City. This type of research is a type of quantitative research. The data collection method in this research used a questionnaire technique, with a sample of 34 respondents The results showed that multiple linear regression Y = 7.481 + 0.197 X1 + X2 + 0.363 X3 + 0.583 X4 + 3.276. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variables Lileadership (X1), Service Quality (X2) Work Environment (X3), Work Motivation (X4) with a value of 0 (zero), Employee Performance (Y) at PT. Sharia People's Credit Bank (BPRS) Fadhila, Bengkulu City. The results of the Leadership test (XI) show tcount 2,402 > ttable ttabel 2.042 and significance 0.002 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning Leadership has a positive and significant effect on Employee Performance at PT. Sharia People's Credit Bank (BPRS) Fadhila, Bengkulu City. The results of the Service Quality test (X2) show tcount 2,147 > ttable ttabel 2.042 and significance 0.004 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Service Quality has a positive and significant effect on Employee Performance at PT. Sharia People's Credit Bank (BPRS) Fadhila, Bengkulu City. The results of the work environment test (X3) show tcount 2.331> ttable ttabel 2.042 and significance 0.007 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning the work environment has a positive and significant effect on Employee Performance at PT. Sharia People's Credit Bank (BPRS) Fadhila, Bengkulu City. The results of the Work Motivation test (X4) show tcount 2.961> ttable ttabel 2.042 and significance 0.006 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Work Motivation has a positive and significant effect on Employee Performance at PT. Sharia People's Credit Bank (BPRS) Fadhila, Bengkulu City. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 11,859 > 2.55, so it can be concluded that accepting the hypothesis, meaning that there is a simultaneous influence between Leadership (XI), Service Quality (X2), Work Environment (X3) Work Motivation (X4 ) on Employee Performance (Y) at PT. Sharia People's Credit Bank (BPRS) Fadhila, Bengkulu City.